Pendidikan Agama Islam di Sekolah Umum (Persfektif Histori) - Juniarti Iryani; Bahaking Rama; Muhammad Yahdi (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this study is to describe and analyze Islamic religious education in public schools in terms of history. The research method used is a qualitative research method with library research (Library research). Source data (primary) in the form of journals and other reading sources relating to the history of Islamic Religious Education in public schools. Data management is entirely "qualitative" because the data encountered is a verbal statement. As for the method of analysis using "inductive" and comparative techniques. The results of this study indicate that Islamic religious education is a "guardian" in achieving national education goals and is also one of the determining factors for student graduation. The implementation of Islamic religious lessons from the colonial period to the reform order era has increasingly had the strength and support of the government in its application in public schools. The strength of Islamic religious education in public schools is further strengthened by the provisions in the law stipulated by the government. Therefore, the existence of religious education in schools will help educators and the government to achieve national education goals.